PENGARUH PEMBERIAN RANSUM DIFERENTASI DENGAN PROBIOTIK BERBASIS SARI DAUN PEPAYA TERHADAP POTONGAN KARKAS KOMERSIAL AYAM KAMPUNG - P. T. B., Ariawan; Siti, N. W.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika, 2016)
This research was carried to determine the weight of commercial carcass pieces of kampung chickens that given fermented ration with probiotic based a papaya leaf extract. The design used in this study was a randomized block design (RBD) with four treatments and four groups as replication so there are 16 experimental units. The treatments were: (A) 70% commercial ration + 30% corn bran as a control, (B) A ration + 8% probiotic based a papaya leaf extract, (C) A ration + 12% probiotic based a papaya leaf extract, and (D) A ration + 16% probiotic based a papaya leaf extract. Variables observed in this research were weight commercial carcass pieces and percentage commercial carcass pieces breast, wings, back, thigh and drumstick of kampung chickens. The results showed that weight of commercial carcass pieces breast, wings, thigh and drumstick tend to increase with increasing the levels of probiotic based a papaya leaf extract, but statistically no significant (P>0.05). Different with the weight of carcass pieces in back parts on treatment D higher significantly (P <0.05) than treatment A, B and C. Based on this research, it can be concluded that probiotic based a papaya leaf extract at levels 16% in the ration did not affect of commercial carcass pieces (breasts, wings, thigh and drumstick), except for the back.
Keywords: probiotic based a papaya leaf extract, commercial carcass pieces, kampung chickens